PENGARUH PENDIDIKAN, UMUR USAHA, OMSET USAHA DAN PENGETAHUAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA MIKRO, KECIL DAN MENENGAH (Studi UMKM Di Kecamatan Anak Ratu Aji Lampung Tengah) - Ayu Laraswati; Yulita Zanaria; Elmira Febri Darmayanti (Jurnal Akuntansi AKTIVA, 2021)
This study aims to determine the effect of education, business age, business turnover and accounting knowledge on the use of accounting information in micro, small and medium enterprises in Anak Ratu Aji District, Central Lampung. The method used in this research is the quantitative method. Respondents in the study 56 business owners, micro, small, and medium. The method of collection is by distributing questionnaires. The results showed that education level, business age, business turnover, and accounting knowledge had a positive and significant effect on the use of accounting information systems.